AN INTERVENTION: SOCIAL EMOTIONAL LEARNING APPROACH ON STUDENT’S SELF-MANAGEMENT - Rosdiani, Rosi; Lestari, Citra (Cirebon International Conference on Education and Economics Proceeding, 2024)
This paper presents intervention findings on student self-management using the Social Emotional Learning (SEL) approach. The participant was one primary student in a class that consisted of fifteen students. The study employed a case study. It was divided into four sections which are observation, assessment, intervention, and monitoring. In collecting data, the researchers used notes from observation, interviews, worksheets, and writing guidelines. The development of student’s self-management was measured through observation from the beginning until monitoring. The interviewees are people who have direct contacts such as classmates, homeroom teacher, and subjects’ teachers. During the intervention, the student was treated using various teaching media such as board games, reading aloud, watching videos, teaching calming down and problem-solving techniques. The indicators of this intervention were (1) The student was able to tell his emotion correctly to his teacher (2) The student was able to calm himself using the calming down technique from intervention treatment (3) The student was able to solve his problem in writing task using the technique given. The result showed that when the student felt angry, the student was able to use his calming down techniques which were drinking water and keeping himself calm in silence (indicator 2). In addition, one day a week the student completed his writing task as his challenging task by making more effort (indicator 3). However, one day in a week, the student showed his anger silently and could not tell his feelings to the teacher.